(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Adverse events following immunization are a major concern which is influencing vaccination coverage all over the world. It is therefore important to evaluate the reporting of this events and factors associated with their occurrence in order to prevent them. Methods: The national database of adverse events following immunization in Albanian children was de-identified and transferred to the IBM® SPSS version 21. (SPSS Inc, USA). Every medical information was re-entered using the Medical Dictionary for Regulatory Activities (MedDRA) terms. The dose-based reporting rates are calculated always taking in consideration the number of administered vaccines instead of the number of distributed ones, which is an advantage of the Albanian reporting system Results: During a thirteen year period (2003-2015) there have been 307 AEFI cases reported for a total of 7,713,325 doses of vaccines administered. That regarded 106 females and 134 males. Most of the events have been reported during 2004. Most of thecases were non-serious (78,8%). Most of the cases were treated at ambulatory setting (72.55), followed by hospital treatment (24.3%) and no treatment (2.6%). Most of the cases were recorded in infants aged < 4 months. Conclusion: During the 13 year period, there were no severe events. The completeness and accuracy of information in the Albanian vaccine safety surveillance system still need to improve.